Peran Kepala Sekolah dalam Pengembangan Pendidikan Karakter di Sekolah Menengah Atas Pangudi Luhur Van Lith Muntilan - wiratno, guntur; Muhdi, Muhdi; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
This research aims to describe: the role of the principal in developing character education at Pangudi Luhur Van Lith Muntilan High School (1) The role of the principal as a manager in developing character values of discipline and social care, (2) The role of the principal as a leader in developing values character of discipline and social care. This research uses a qualitative approach with a qualitative type. Data were collected using interviews, observation and documentation methods, while data validation was carried out through triangulation. Based on the results of research and discussion of the role of school principals as managers and leaders in the development of disciplined character education and social care, it can be concluded: (1) planning program creation by identifying problems by conducting SWOT, coordinating between fields, availability of program funds, socialization of programs through meetings work, parent meetings, through teaching and learning activities and during MPLS. (2) Organizing, dividing tasks and authority, granting decrees. (3) Implementation, integrating character in learning or in school culture. (4) Supervision, carried out with direct involvement, coordination, accountability. (5) Providing an example by being present on time, dressing neatly, following the 5S greetings, and being directly involved in social action activities. (6) Providing motivation to carry out morning briefings providing 5S, being directly involved in social action activities, through flag ceremonies, and coaching. It is recommended that all Pangudi Luhur Van Lith Muntilan High School students be actively involved in accordance with their respective duties and roles in developing character education and in providing role models and providing motivation in implementing character education development. Keywords: Role of the school principal, character education, discipline character and social care